Acupuncture for neuropathic pain: A meta-analysis of randomized control trials - Feng, Zitong; Cui, Shaoyang; Yang, Huijun; Wang, Yixiao; Zhou, Xuan; Wong, John; Lai, Liting; Yang, Zeyu; Huang, Bingjing; Zheng, Huiyan; Xu, Mingzhu (Frontiers in Neurology, 2023)
Background Neuropathic pain (NP) is expected to increase due to the high risk of global population aging. Acupuncture has a definite clinical effect on NP. Therefore, a systematic review and meta-analysis were conducted to evaluate the effect on pain intensity and safety of acupuncture in patients with NP. Methods An encompassing search of specific authoritative databases in English, from their inception to 2022, was performed. The databases were as follows: Scopus, Ovid EMBASE, Ovid Cochrane Database of Systematic Reviews, Ovid Cochrane Central Register of Controlled Trials, Ovid MEDLINE(R) and Epub Ahead of Print, In-Process and Other Non-Indexed Citations, and Daily. All the randomized controlled trials regarding the acupuncture treatment of NP will be included. Methodological quality assessment of the included trials was assessed based on the risk of bias from the Cochrane handbook. A meta-analysis was performed for the main outcomes. In addition, sensitivity analysis, subgroup analysis, and funnel plot were also carried out. Results A total of 16 studies with 1,021 patients with NP were evaluated in a systematic review. According to the results of the overall meta-analysis in eight RCTs with 338 participants, the acupuncture group was better than the control group in improving changes in pain intensity (SMD −0.59, 95% CI: −0.95 to −0.23, P = 0.001). In subgroup analysis, five trials indicated that acupuncture was more effective in improving changes in pain intensity than sham acupuncture (SMD −0.54, 95% CI: −0.95 to −0.13, P = 0.01), two trials evaluated the effect on changes in pain intensity in the comparison of acupuncture and conventional treatments, no significant difference existed (SMD −0.61, 95% CI: −1.83 to 0.61, P = 0.33), and one trial compared acupuncture with blank control evaluating the effect of changes in pain intensity with a significant difference. Eleven studies mentioned the safety conditions and acupuncture-induced AEs were mild and reversible. Both the sensitivity analysis and funnel plot analysis showed that the meta-analysis was stable and irreversible without publication bias. The GRADE was rated as “very low.” Conclusion The acupuncture group had higher effectiveness than sham intervention or blank control for changes in pain intensity, but there is no significant difference between acupuncture and conventional treatments in treating NP. The acupuncture-induced adverse events were mild and reversible. However, the interpretation of our results should be performed cautiously due to the low methodological quality of selected publications. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022306461.